PENGARUH PENERIMAAN TEKNOLOGI TERHADAP PENGGUNAAN APLIKASI INVESTASI ONLINE BIBIT DI KALANGAN REMAJA - Al-Fawwaz, Muhammad Alif; Effendi, R. Nabila Fitri; Yulianti, Riri Aryani (Universitas Wiralodra, 2023)
Investment is a very profitable business financially. With the benefits, this has made teenagers now starting to be interested in investing. In addition, technological developments have made investing very popular nowadays and can be done very easily and flexibly. One investment that is widely used by teenagers is mutual funds. Mutual funds are a container that is used as a collection of funds from investors to be invested in the securities portfolio of an investment manager. Along with technological developments, the number of teenagers investing in mutual funds has also increased. This is influenced by the acceptance of technology among teenagers. This research examines the influence of technology acceptance on the use of online seed investment applications among teenagers. In the context of ease of accepting technology, the use of online applications for investing is a consideration for teenagers in personal financial management. Teenagers, as potential investors, are exposed to technology that makes it easier for them as beginners in the investment process. The data used is in the form of questionnaire results distributed to a sample of teenagers who use the Bibit online investment application. Data collection was implemented using an online questionnaire which included questions related to technology acceptance and behavior in using online investment applications. The analytical tool applied is simple linear regression which is preceded by a validity test, a reliability test, then a classical assumption test. This research aims to provide in-depth insight into how technology influences the use of online seed investment applications among teenagers.